Overcoming Parent Strategies with Down Syndrome (DS) Children - Tania Nurmalita (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2019)
Being a part of the family who has children with special needs like Down Syndrome (DS) of course really challenging for facing daily activities with children with DS around. The aim of this literature review is to reveal about how parents of children with DS applied coping strategy to face daily life and support their child. The sources were collected online from 4 journals databases. Those databases are ProQuest, SAGE Journals, Science Direct, and ERIC. Articles that were taken by researcher were published in year 2009-2019. Researcher found 179 journals and selected by screening inclusion and exclusion criteria, the final amount of conducted and reviewed journals are 12 papers. Based on review that had been done, all of the parents of children with DS did some kinds of coping strategy in parenting. The strategies that used are: attribution technique in accepting their child’s condition, implementing the positive attitude towards their children’s condition, getting more intense in religious activity and got closer to God, looking for the organization and community that related to DS, and also doing more sports or outdoor activity as a coming out purpose. Finding out the parents’ coping strategy and the impact for the DS child will be the basis of conducting parenting program effectively and hopefully this program will be effective in optimizing the development of DS child.